Immunolocalization of Advanced Glycation End Products, Mitogen Activated Protein Kinases, and Transforming Growth Factor-β/Smads in Pelvic Organ Prolapse. (September 2018) - Vetuschi, Antonella; Pompili, Simona; Gallone, Anna; D'Alfonso, Angela; Carbone, Maria Gabriella; Carta, Gaspare; Festuccia, Claudio; Gaudio, Eugenio; Colapietro, Alessandro; Sferra, Roberta
Collagen and matrix metalloproteinases (MMP) play a pivotal role in the pathophysiology of Pelvic Organ Prolapse (POP) as a switch between type I and III collagen together with a simultaneous activation of MMPs have been observed in the vaginal wall. The aim of this study was to evaluate the Advanced Glycation End (AGE) products, ERK1/2 and transforming growth factor (TGF)-β/Smad pathway expression in muscularis propria in women with POP compared with control patients. We examined 20 patients with POP and 10 control patients treated for uterine fibromatosis. Immunohistochemical analysis using AGE, RAGE, ERK1/2, Smads-2/3, Smad-7, MMP-3, and collagen I-III, TIMP, and α-SMA were performed. Smad-2/3, Smad-7, AGE, ERK1/2, p-ERK, and p-Smad3 were also evaluated using Western-blot analysis. POP samples from the anterior vaginal wall showed disorganization of the normal muscularis architecture. In POP samples, AGE, ERK1/2, Smad-2/3, MMP-3, and collagen III were upregulated in muscularis whereas in controls, Smad-7 and collagen I were increased. The receptor for AGEs (RAGE) was mild or absent both in controls and prolapse. We demonstrated the involvement of these markers in women with POP but further studies are required to elucidate if the overexpression of these molecules could play a crucial role in the pathophysiology of POP disease.